Relevance of Technical and Vocational Education and Training in the Employability of Computer Science Graduates - Meneses III, Jesus Mercado (Jurnal Pendidikan Progresif, 2023)
Relevance of Technical and Vocational Education and Training in the Employability of Computer Science Graduates. Objectives: A study was conducted to determine the relevance of Technical Education and Skills Development National Certification in relation to the employment/employability of computer science graduates of Eastern Samar State University, Philippines. Methods: A descriptive-correlational design was used and data was analyzed through mean, frequency and percentage distribution. A null hypothesis was tested using Cramer’s V association method to determine if there exist a correlation. Findings: The results showed that most graduates were employed, a significant number were National Certificate II (NC II) competency test passers, and many considered "not being prepared" as the major hindrance for not taking the said exam. Conclusion: the majority of graduates found NC II to be important in securing their current job and Cramer’s V score showed strong correlation and rejected the null hypothesis. Based on these findings, it is recommended that efforts to improve graduates' preparation for NC II exams should be continued or even intensified.Keywords: tvet, tesda, skills training, national skill’s certification, employability, computer science.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202338